Pengaruh Komunikasi pada Pembelajaran CTL terhadap Aspek Kognitif Siswa Kelas V SDN Sriombo Lasem - Fiky Septia Rahmawati (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
This research aims to determine the Effect of Communication on CTL Learning on the Cognitive Aspects of Class V Students at SDN Sriombo Lasem Rembang Even Semester 2021/2022 which can be seen in learning and communication outcomes. By using a quantitative approach and This research is in the form of a Pre-Experimental Design with a One-Group Pretest-Posttest Design. The research population was all fifth grade students at SDN Sriombo Lasem Rembang even semester 2021/2022. The sample to be taken is 15 fifth grade students using a purposive sampling technique. The data in this study were obtained through tests and observations. The researchers concluded that there was a very significant influence on communication in CTL learning, there were cognitive aspects of fifth grade students at SDN Sriombo Lasem Rembang, Even Semester 2021/2022. As for the completeness of student learning from the data obtained, it was found that the fifth grade students at SDN Sriombo did not complete it even though there was a very significant influence of communication.